Antibacterial photochromic polypropylene masterbatch, and preparation method and application thereof

CN123004035APending Publication Date: 2026-10-30KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611421277.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本发明意在提供一种抗菌光致变色聚丙烯母粒及其制备方法与应用,以解决现有技术中光致变色PP材料变色/消色速度慢、抗菌性能不足、加工热稳定性差以及难以满足食品接触安全标准的问题

Benefits of technology

1、快速光致变色响应:通过优选有机光致变色材料或有机-无机复合体系,实现变色响应时间≤30秒,消色时间≤60秒。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123004035A_ABST
    Figure CN123004035A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of plastic modification and processing, and discloses an antibacterial photochromic polypropylene master batch as well as a preparation method and application thereof.The raw materials of the master batch, in mass parts, comprise polypropylene resin carriers 60-85 parts, photochromic materials 0.5-10 parts, antibacterial agents 1-5 parts, dispersants 0.5-3 parts, antioxidants 0.1-1 part, processing aids 0.5-2 parts and nano-enhanced fillers 2-10 parts.The master batch is prepared through a melt extrusion process, and the obtained master batch has a fast photochromic response (color change is less than or equal to 30 seconds, and color elimination is less than or equal to 60 seconds), high antibacterial efficiency (an antibacterial rate is greater than or equal to 99.9%) and excellent food contact safety (a total migration amount is less than or equal to 10 mg / dm2). The master batch prepared by the application can be directly blended and injection molded with PP resins, and is suitable for the field of intelligent food packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of plastic modification and processing technology, specifically to an antibacterial photochromic polypropylene masterbatch, its preparation method, and its application. Background Technology

[0002] Polypropylene (PP) is widely used in food packaging due to its good mechanical properties, chemical resistance, and cost advantages. However, ordinary PP packaging lacks intelligent response (such as photochromism) and antibacterial functions, making it difficult to meet the increasing demands for food freshness indication and hygiene safety.

[0003] Photochromic materials can be classified into organic (such as spiropyran, spiroxazine, and azobenzene) and inorganic (such as transition metal oxides). Organic materials exhibit rapid color-changing response but poor thermal stability; inorganic materials demonstrate good stability but slow color-changing / decolorization rates. In existing technologies, blending photochromic materials with polypropylene (PP) often encounters problems such as uneven dispersion, low color-changing efficiency, insufficient processing thermal stability, and interference between antibacterial agents and the color-changing components.

[0004] Furthermore, food packaging materials must comply with the GB 4806 series of food safety standards to ensure compliance with migration and sensory indicators. Therefore, developing a PP masterbatch that simultaneously possesses rapid photochromic response, high-efficiency antibacterial properties, and meets food contact requirements has significant application value. Summary of the Invention

[0005] The present invention aims to provide an antibacterial photochromic polypropylene masterbatch, its preparation method and application, in order to solve the problems of slow color change / decolorization speed, insufficient antibacterial properties, poor processing thermal stability and difficulty in meeting food contact safety standards in the existing photochromic PP materials.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: an antibacterial photochromic polypropylene masterbatch, the raw materials comprising, by weight, 60-85 parts of polypropylene resin carrier, 0.5-10 parts of photochromic material, 1-5 parts of antibacterial agent, 0.5-3 parts of dispersant, 0.1-1 parts of antioxidant, 0.5-2 parts of processing aid, and 2-10 parts of nano-reinforcing filler.

[0007] Preferably, as an improvement, the photochromic material is one of organic photochromic materials, inorganic photochromic materials, and organic-inorganic composite photochromic materials; the organic photochromic material is at least one of spiropyran derivatives, spiroxazine derivatives, azobenzene derivatives, and diarylethylene derivatives; the inorganic photochromic material is at least one of nano-WO3, nano-TiO2, and calcium fluoride doped with rare earth ions; and the organic-inorganic composite photochromic material is a spiropyran / nano-TiO2 hybrid material or an azobenzene / montmorillonite intercalated composite material.

[0008] Preferably, as an improvement, the antibacterial agent is a silver-zinc inorganic antibacterial agent, a silver ion antibacterial agent, or a zinc ion antibacterial agent.

[0009] Preferably, as an improvement, the antioxidant is at least one of hindered phenolic antioxidants and phosphite antioxidants.

[0010] Preferably, as an improvement, the antioxidant is a compound system of hindered phenolic antioxidants and phosphite antioxidants.

[0011] Preferably, as an improvement, the processing aid includes at least one of zinc stearate, white oil, and solid paraffin; the nano-reinforcing filler is at least one of nano talc, nano titanium dioxide, and nano kaolin.

[0012] Preferably, as an improvement, a method for preparing antibacterial photochromic polypropylene masterbatch includes the following steps: S1. Weigh the polypropylene resin, photochromic material, antibacterial agent, dispersant, antioxidant, processing aid and nanofiller according to the formula ratio; S2. Mix the above raw materials in a high-speed mixer; S3. The mixture is fed into a twin-screw or four-screw extruder, and after melt blending, extrusion, water cooling and pelletizing, masterbatch granules are obtained.

[0013] Preferably, as an improvement, in step S3, the extrusion process parameters are: screw temperature 180-230℃, main machine speed 200-400 r / min, and vacuum degree -0.05 to -0.08 MPa.

[0014] Preferably, as an improvement, the application of an antibacterial photochromic polypropylene masterbatch in the preparation of food packaging materials.

[0015] The principle and advantages of this solution are: in practical applications, it addresses the problems of slow color change / fading speed, insufficient antibacterial properties, poor processing thermal stability, and difficulty in meeting food contact safety standards of photochromic PP materials in existing technologies. This technical solution utilizes an antibacterial photochromic polypropylene masterbatch specifically designed for injection molding of food packaging boxes. The formulation comprises seven components in specific mass proportions: a polypropylene resin carrier, photochromic material, antibacterial agent, dispersant, antioxidant, processing aid, and nano-reinforcing filler. The proportions and selection of each component are designed around six core constraints unique to the food packaging industry: food contact safety compliance, high-temperature extrusion processing stability, reversible intelligent color-changing indication under light, long-lasting antibacterial hygiene, mechanical strength of finished packaging, and low additive migration limits. The components form a complementary and balanced compound system, systematically addressing multiple industry pain points of existing modified polypropylene materials, including slow photochromic response, high-temperature failure of antibacterial components, dispersion and aggregation of functional fillers, thermal degradation of color-changing molecules during high-temperature processing, excessive additive migration failing to meet national food contact standards, and decreased packaging mechanical properties.

[0016] The polypropylene resin carrier, serving as the matrix of the masterbatch, is the fundamental continuous phase of the entire formulation. Its material selection and proportioning design are fully aligned with the processing and usage characteristics of food packaging. The melt flow properties of food-grade homopolymer, block copolymer, and random copolymer polypropylene are highly matched with the 180–230°C processing temperature range of the masterbatch extrusion. This ensures its melt flow properties are suitable for injection molding processes of various food packaging boxes, such as fresh produce containers and fast food containers. Different types of polypropylene can also flexibly adjust the rigidity and low-temperature toughness of the finished packaging, adapting to diverse food usage scenarios such as refrigeration and short-term microwave heating. The new food-grade polypropylene substrate itself meets the basic compliance requirements of GB 4806.7-2023 for food contact materials, forming a physical barrier to bind internal photochromic and antibacterial functional additives, significantly reducing the risk of additive migration into the food medium. Simultaneously, the high proportion of resin carrier means that this masterbatch requires only 5% of its components. With a low addition ratio, it can be blended with pure polypropylene for injection molding without modifying existing mature food packaging production lines, making it highly convenient to use. Unlike the design concept of ordinary industrial modified masterbatch that can use recycled polypropylene, this solution strictly limits the use of brand-new food-grade polypropylene raw materials, avoiding food safety hazards from the source of residual heavy metals and harmful small molecules released from recycled materials.

[0017] Photochromic materials are the core functional components for intelligent visual indication of food freshness. Addressing the industry contradictions of poor thermal stability in single organic photochromic materials and slow color change and decolorization rates in single inorganic photochromic materials, the formulation offers three optional systems: organic, inorganic, and organic-inorganic composites, suitable for different food packaging scenarios. Organic derivatives such as spiropyran, spiroxazine, azobenzene, and diarylethylene rely on reversible molecular photoisomerization reactions to achieve color development and decolorization. Under 365nm ultraviolet light irradiation, the color change time can be controlled within 30 seconds, and decolorization is completed within 60 seconds in a light-protected environment. They exhibit high color change sensitivity and are suitable for packaged products such as fresh produce and fruits that rely on light to monitor freshness. However, pure organic color-changing molecules are prone to molecular decomposition and failure under extrusion temperatures above 180℃. Inorganic derivatives such as nano-tungsten trioxide, nano-titanium dioxide, and rare-earth-doped calcium fluoride rely on… Metal oxide lattice photocatalytic carrier migration achieves color change, exhibiting excellent thermal stability and no performance degradation during high-temperature processing. However, its drawback lies in the slow lattice response kinetics, with a decolorization time exceeding 85 seconds, making it more suitable for packaging dry goods requiring long-term light-proof storage. Spiropyran / nano-titanium dioxide hybrid and azobenzene / montmorillonite intercalated organic-inorganic composite photochromic materials are the optimal system for this formulation. The inorganic nanocarrier physically encapsulates and isolates organic color-changing molecules from high-temperature and oxygen environments, inhibiting the thermal degradation of organic components while fully preserving the rapid and reversible color change advantage of organic molecules. This balances processing stability and color change response efficiency, meeting the requirements of most food packaging environments involving cyclic light exposure and alternating hot and cold temperatures. Furthermore, all three types of photochromic materials are selected from modified varieties with no heavy metal precipitation and low migration, meeting the stringent requirements for food contact safety.

[0018] Silver-zinc inorganic antibacterial agents, silver ion antibacterial agents, or zinc ion antibacterial agents fulfill the core function of long-lasting antibacterial action in food packaging. Food packaging comes into direct contact with fresh ingredients and is highly susceptible to the growth of pathogenic bacteria such as Escherichia coli and Staphylococcus aureus. The inorganic silver-zinc composite antibacterial system can stably release trace amounts of metal ions to disrupt bacterial cell membranes and inhibit microbial metabolism. It maintains a stable antibacterial rate of over 99.9% against these two common pathogenic bacteria after 24 hours of contact. Unlike organic antibacterial agents, which are prone to high-temperature decomposition and large-scale migration into food, the inorganic antibacterial carrier structure can restrict the release rate of metal ions, controlling the amount of metal migration below the national standard limit. At the same time, it works synergistically with dispersants and antioxidants to avoid mutual interference and activity decay between antibacterial components and photochromic materials during high-temperature extrusion. This makes it suitable for the special characteristics of food packaging, such as long-term storage and repeated opening and closing in contact with food.

[0019] Polyethylene wax, polyoxyethylene alkylphenol ether, or maleic anhydride-grafted polypropylene dispersants solve the problem of functional filler agglomeration. Photochromic nanoparticles, inorganic antibacterial powders, and nano-reinforced fillers are all nanoscale powders. Direct dry mixing with polypropylene easily leads to agglomeration and clumping, which not only significantly reduces color-changing efficiency and weakens antibacterial properties but also causes pitting and color differences on the surface of injection-molded food boxes. The dispersant is compatible with polypropylene resin on one end and adsorbs onto the surface of nanoparticles on the other end, achieving uniform pre-dispersion of powders during the high-speed mixing stage. During extrusion, it further removes agglomerated particles, allowing various functional components to be evenly distributed in the matrix. Test comparison results show that the color-changing efficiency and cycle stability of the material are significantly reduced after removing the dispersant. At the same time, food-grade compliant dispersants are used, eliminating the risk of toxic small molecule migration and making it suitable for food contact scenarios.

[0020] The preferred formulation of hindered phenolic and phosphite antioxidants is a 1:2 blend, specifically designed to address two scenarios: high-temperature melting processing of food packaging masterbatches and long-term storage aging. Polypropylene resin and organic photochromic molecules are prone to thermo-oxidative degradation with oxygen at screw extrusion temperatures of 180–230°C, leading to a decrease in matrix mechanical properties and the failure of color-changing components. Hindered phenolic antioxidants capture free radicals, while phosphite antioxidants decompose hydrogen peroxide. The combination of these two forms a synergistic antioxidant system, which dually inhibits the oxidative decomposition of resin and functional additives under the extrusion vacuum environment. This ensures that there is no significant attenuation of masterbatch color change and antibacterial properties after processing. At the same time, the amount of antioxidant components added is extremely low, which will not cause the total migration to exceed the standard, meeting the migration limits requirements of GB 4806 series food contact materials.

[0021] During the technical solution development phase, the contradiction between photochromic materials and the heat-resistant processing properties of PP was one of the key challenges. Photochromic materials, especially spiropyran and spiroxazine organic photochromic agents, are prone to molecular ring-opening failure, photoresponsive group breakage, and decreased color-changing sensitivity at polypropylene extrusion temperatures of 180–230°C. However, industrial production of PP masterbatch requires high-temperature melt extrusion. Therefore, this invention needs to simultaneously meet the performance requirements of high-temperature processing stability and rapid color-changing response, a long-standing contradiction in the field. This solution employs an organic photochromic agent + nano-TiO2 hybrid system + antioxidant system to form a composite protective effect, ensuring the photochromic agent maintains high color-changing efficiency even after a single extrusion. Furthermore, the inventors discovered that while silver ions have high reactivity, directly using ordinary silver-based antibacterial agents can easily affect the electronic structure of photochromic molecules, leading to decreased color development efficiency and accelerated aging of the photochromic agent. This results in improved antibacterial performance but decreased photochromic properties. To avoid interference between the antibacterial agent and the photochromic agent, this technical solution uses a silver-zinc-loaded inorganic antibacterial agent, which utilizes an inorganic carrier to slowly release metal ions, maintaining an antibacterial rate of over 99.9% while keeping the color-changing performance largely unaffected.

[0022] In addition, the study found that the type of photochromic material directly affects the color change rate, decolorization rate and cycle stability of the material. This technical solution achieves the above-mentioned dimensions by optimizing the photochromic system and coordinating with the antioxidant system (1010+168 (1:2)). It can not only ensure the retention rate of the color change agent after processing, but also achieve the retention rate of antibacterial agent activity and long-term storage stability.

[0023] In summary, the beneficial effects of this technical solution are as follows: 1. Rapid photochromic response: By selecting organic photochromic materials or organic-inorganic composite systems, the color change response time is ≤30 seconds and the decolorization time is ≤60 seconds.

[0024] 2. Highly effective antibacterial properties: It uses silver-zinc loaded inorganic antibacterial agent, with an antibacterial rate of ≥99.9% against Escherichia coli and Staphylococcus aureus.

[0025] 3. Food contact safety: The masterbatch meets the requirements of GB 4806.7-2023, with a total migration of ≤10 mg / dm³. 2 The amount of heavy metal migration is below the limit.

[0026] 4. Processing stability: Through the synergistic effect of dispersants and antioxidants, the performance of photochromic materials and antibacterial agents is ensured not to degrade during high-temperature extrusion.

[0027] 5. Ease of application: The masterbatch can be directly mixed with PP resin and then injection molded without any additional modification steps. Attached Figure Description

[0028] Figure 1 This is a schematic diagram of the structure of the photochromic polypropylene masterbatch of inorganic antibacterial agent particles in Example 1.

[0029] Figure 2 This is a schematic diagram of the structure of the photochromic polypropylene masterbatch for the anionic antibacterial agent particles in Example 2.

[0030] Figure 3 This is a schematic diagram of the structure of the photochromic polypropylene masterbatch for example 3, which contains zinc ion antibacterial agent particles. Detailed Implementation

[0031] The following detailed description provides further details on specific embodiments, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the technical means used in the following embodiments are conventional means well known to those skilled in the art; the experimental methods used are all conventional methods; and the materials and reagents used are all commercially available.

[0032] Overview of the plan: An antibacterial photochromic polypropylene masterbatch comprises the following components by weight: 60-85 parts polypropylene resin carrier, 0.5-10 parts photochromic material, 1-5 parts antibacterial agent, 0.5-3 parts dispersant, 0.1-1 parts antioxidant, 0.5-2 parts processing aid, and 2-10 parts nano-reinforcing filler.

[0033] Among them, the photochromic material is selected from at least one of the following: Organic photochromic materials: at least one of spiropyran derivatives, spiroxazine derivatives, azobenzene derivatives, and diarylethylene derivatives; Inorganic photochromic materials: at least one of nano WO3, nano TiO2, and calcium fluoride doped with rare earth ions; Organic-inorganic composite photochromic materials: spiropyran / nano-TiO2 hybrid materials or azobenzene / montmorillonite intercalation composite materials.

[0034] The antibacterial agent is a silver-zinc inorganic antibacterial agent, a silver ion antibacterial agent, or a zinc ion antibacterial agent.

[0035] The dispersant is polyethylene wax, polyoxyethylene alkylphenol ether, or maleic anhydride-grafted polypropylene.

[0036] The antioxidant is at least one of hindered phenols (such as B215) and phosphites, preferably a combination of the two, with the optimal ratio of the two being 1:2.

[0037] Processing aids include at least one of zinc stearate, white oil, and solid paraffin.

[0038] The nano-reinforcing filler is at least one of nano-talc, nano-titanium dioxide, and nano-kaolin.

[0039] A method for preparing an antibacterial photochromic polypropylene masterbatch includes the following steps: S1. Weigh the polypropylene resin, photochromic material, antibacterial agent, dispersant, antioxidant, processing aid and nanofiller according to the formula ratio; S2. Add the above raw materials into a high-speed mixer and mix at room temperature for 5-10 minutes; S3. The mixture is fed into a twin-screw or four-screw extruder, and after melt blending, extrusion, water cooling, and pelletizing, masterbatch granules are obtained. The extrusion process parameters are: screw temperature 180-230℃, main extruder speed 200-400 r / min, and vacuum degree -0.05 to -0.08 MPa.

[0040] Example 1 An antibacterial photochromic polypropylene masterbatch comprises the following components by weight: Homopolymer polypropylene (HP500P): 75 parts; Spiropyran derivatives (photochromic materials): 3 parts; Silver-zinc inorganic antibacterial agent (Ag-Zn content 15%): 2 parts; Polyethylene wax (dispersant): 1.5 parts; Antioxidant B215: 0.3 parts; Zinc stearate (processing aid): 0.8 parts; Nano talc powder (reinforcing filler): 5 parts.

[0041] A method for preparing an antibacterial photochromic polypropylene masterbatch includes the following steps: S1. After drying the nano talc powder at 110℃ for 4 hours, mix all the raw materials in proportion. S2. Add the raw materials to a high-speed mixer and mix at 800 r / min for 8 minutes to obtain a mixture; S3. Feed the mixture into a co-rotating twin-screw extruder (L / D=40:1), set the temperature as follows: Zone 1 180℃, Zone 2 200℃, Zone 3 210℃, Zone 4 205℃, Die head 200℃, main extruder speed 300 r / min, vacuum degree -0.06 MPa; the extruded strip is water-cooled, pelletized, and dried to obtain masterbatch, the structural diagram of which is shown below. Figure 1 As shown.

[0042] Example 2 The difference between this embodiment and Embodiment 1 is that: in this embodiment, an antibacterial photochromic polypropylene masterbatch comprises the following components by weight: Block copolymer polypropylene (K7726H-RC): 70 parts; Nano WO3 (photochromic material): 5 parts; Silver ion antibacterial agent (Ag content 5%): 3 parts; Polyoxyethylene alkylphenol ether (dispersant): 2 parts; Antioxidant (10¹⁰ / 16⁸ = 1:2): 0.4 parts; White oil (processing aid): 1.2 parts; Nano titanium dioxide (reinforcing filler): 3 parts.

[0043] The preparation process is basically the same as in Example 1, except that the extrusion temperature conditions in this example are: Zone 1 temperature 190℃, Zone 2 temperature 200℃, Zone 3 temperature 210℃, Zone 4 temperature 220℃, and die head temperature 220℃; the structural schematic diagram of the prepared masterbatch is shown below. Figure 2 As shown.

[0044] Example 3 The difference between this embodiment and Embodiment 1 is that: in this embodiment, an antibacterial photochromic polypropylene masterbatch comprises the following components by weight: Random copolymer polypropylene (SP-179): 80 parts; Spirooxazine / nano-TiO2 hybrid material (photochromic material): 4 parts (where spirooxazine:TiO2 = 1:1); Zinc ion antibacterial agent (ZnO content 20%): 2.5 parts; Maleic anhydride-grafted polypropylene (dispersant): 1.8 parts; Antioxidant B215: 0.25 parts; Solid paraffin (processing aid): 1.0 part; Nano-kaolin (reinforcing filler): 4 parts.

[0045] The preparation process is the same as in Example 1, and the structural schematic diagram of the prepared masterbatch is shown below. Figure 3 As shown.

[0046] Comparative Example 1 The difference between this comparative example and Example 1 is that no photochromic material was added in this comparative example.

[0047] Comparative Example 2 The difference between this comparative example and Example 1 is that no silver-zinc inorganic antibacterial agent was added in this comparative example.

[0048] Comparative Example 3 The difference between this comparative example and Example 1 is that no dispersant was used in this comparative example, and the spiropyran derivative was directly dry-mixed with PP and then extruded.

[0049] Comparative Example 4 The difference between this comparative example and Example 1 is that the silver-zinc inorganic antibacterial agent (Ag-Zn content 15%) is replaced with an equal mass of conventional organic antibacterial agent OBPA (10,10'-oxobisphenoxarsenic, effective content 5%), while the remaining components and preparation process are the same as in Example 1.

[0050] Comparative Example 5 The difference between this comparative example and Example 1 is that the spiropyran derivative is replaced with an equal mass of single nano-WO3 (particle size 30-50nm), while the other components and preparation process are the same as in Example 1.

[0051] Comparative Example 6 The difference between this comparative example and Example 1 is that antioxidant B215 was not added in this comparative example, while the other components and preparation process are the same as in Example 1.

[0052] Comparative Example 7 The difference between this comparative example and Example 3 is that: in this comparative example, the spiroxazine / nano-TiO2 hybrid material is replaced with an equal mass of pure spiroxazine (i.e., no nano-TiO2 carrier is introduced, and the photochromic material is all organic spiroxazine 4 parts), and the other components and preparation process are the same as in Example 3.

[0053] Experimental Performance Testing The masterbatches from each embodiment and comparative example were mixed with pure PP resin at a ratio of 5:95, and injection molded into standard test strips (size: 50×50×2 mm) and antibacterial test pieces. The following tests were conducted, with each group undergoing three repeated tests. The test indicators, test methods, and test results are shown in Table 1. Table 1 Test Project Test standards / methods Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Color change response time (s) GB / T 26397-2011, 365 nm UV irradiation until ΔE*ab reaches 90% of its maximum value. 25 45 28 - 26 38 26 52 34 25 Decolorization time (s) Time required to restore to 80% of initial color intensity under dark conditions 50 85 55 - 52 75 52 110 72 42 Color-changing efficiency (ΔE*ab) Ultraviolet-visible spectrophotometry is used to measure the color difference before and after illumination. 35.2 28.5 32.8 0.5 34.8 22.4 34.5 26.3 24.5 36.8 Cyclic stability (efficiency retention rate after 500 cycles) ISO 8980-3, Light-Fading Cycle 92 96 94 - 91 78 88 95 68 70 ΔE*ab retention rate (%) after high-temperature processing % 78 96 90 / 79 70 72 97 55 62 Antibacterial rate of Escherichia coli (%) ISO 22196, 24-hour contact 99.95 99.98 99.96 99.93 5.2 99.9 92.8 99.94 99.91 99.95 Antibacterial rate against Staphylococcus aureus (%) ISO 22196, 24-hour contact 99.93 99.96 99.94 99.91 4.8 99.88 91.6 99.92 99.89 99.93 <![CDATA[Overall migration (mg / dm 2 )]]> GB 31604.8, 4% acetic acid, 40℃ × 10 d 8.2 7.5 8 8.5 8.3 9.8 12.5 8 11.2 9.6 Lead migration (mg / kg) GB 31604.1, ICP-MS <0.01 <0.01 <0.01 <0.01 <0.01 <0.01 <0.01 <0.01 <0.01 <0.01 Cadmium migration (mg / kg) GB 31604.1, ICP-MS <0.005 <0.005 <0.005 <0.005 <0.005 <0.005 <0.005 <0.005 <0.005 <0.005 Tensile strength (MPa) GB / T 1040.2 32.5 30.8 33.2 33 32.8 29.5 31.8 32 28.3 31.5 <![CDATA[Impact strength (kJ / m 2 )]]> GB / T 1843 6.8 6.2 7 7.1 6.9 5.8 6.5 6.4 5.2 6.5 Note: The "ΔE*ab retention rate" index after high-temperature processing is tested by the following method: after heat-treating the masterbatch at 230℃ for 10 minutes, the ΔE*ab is measured by the aforementioned UV-Vis spectrophotometry. The ratio of the ΔE*ab of the masterbatch to that of the untreated sample is used to evaluate the high-temperature processing tolerance of the photochromic component.

[0054] As shown in Table 1, Examples 1-3 all exhibited rapid color change response (≤45 s) and decolorization (≤85 s). Among them, the organic system (Example 1) and the organic-inorganic composite system (Example 3) had the fastest response, meeting the requirements of "rapid color change sensitivity and decolorization speed". The antibacterial rate of all examples was ≥99.9%.

[0055] Comparing the formulation and process differences between Examples 1 to 3: the three examples respectively adopted three technical routes in the selection of photochromic materials: organic, inorganic, and organic-inorganic composite, forming a gradient scheme layout. Example 1 uses homopolymer polypropylene HP500P as a carrier, combined with spiropyran derivative as a pure organic photochromic component, silver-zinc loaded inorganic antibacterial agent, polyethylene wax dispersant, antioxidant B215, zinc stearate processing aid, and nano talc reinforced filler; Example 2 uses block copolymer polypropylene K7726H-RC, with nano tungsten trioxide as a pure inorganic photochromic component, the antibacterial agent is adjusted to a silver ion antibacterial agent, and the dispersant, processing aid, and nano filler are replaced with polyoxyethylene alkylphenol ether, white oil, and nano titanium dioxide, respectively; Example 3 uses random copolymer polypropylene SP-179, the photochromic component is a hybrid material composed of spiroxazine and nano titanium dioxide in a 1:1 mass ratio, and the remaining components are adjusted accordingly to zinc ion antibacterial agent, maleic anhydride grafted polypropylene dispersant, solid paraffin processing aid, and nano kaolin. Therefore, the three embodiments cover almost all the possible types of components in the claims, supporting the broad scope of protection claimed by the claims from the perspectives of different resin matrices, different color-changing systems, different antibacterial systems, and different combinations of dispersants and processing aids. In terms of the preparation process, Examples 1 and 3, as well as Comparative Examples 1 to 7, all used completely identical extrusion process parameters: Zone 1 180°C, Zone 2 200°C, Zone 3 210°C, Zone 4 205°C, die head 200°C, main engine speed 300 r / min, and vacuum degree -0.06 MPa. Only Example 2, due to the higher melt energy required for dispersing the inorganic nano-tungsten trioxide powder system, increased the overall extrusion temperature range to 190 to 220°C. This design, which introduces no additional process variables besides the formulation, ensures that the performance differences of each group can be uniquely attributed to the formulation itself, making the comparative conclusions fully comparable. Furthermore, Example 2's temperature range is still within the 180 to 230°C range defined in the claims, and it also obtained qualified products, further demonstrating that this process window has good adaptability to different color-changing systems.

[0056] The test results show that Example 1 has the shortest color-changing response time of 25 seconds and a decolorization time of 50 seconds, with a color-changing efficiency ΔE*ab of 35.2, demonstrating excellent light response speed. However, its ΔE*ab retention rate after high-temperature processing is only 78%, and the efficiency retention rate after 500 cycles is 92%, indicating relatively limited heat resistance and fatigue resistance. Example 2 has the highest cycle stability (96%) and ΔE*ab retention rate after high-temperature processing (96%), showing the most outstanding thermal stability. However, its color-changing response time is extended to 45 seconds, the decolorization time is as long as 85 seconds, and the color-changing efficiency drops to 28.5, indicating a significantly insufficient response speed. Example 3 achieves a balance between the two, with a color-changing response time of 28 seconds and a decolorization time of 55 seconds, which is basically equivalent to the pure organic system. After high-temperature processing, the ΔE*ab retention rate reaches 90%, and the cycle retention rate is 94%, which is significantly better than the pure organic system and close to the pure inorganic system. The above results confirm the inherent contradiction between single organic photochromic materials, which have fast response but poor thermal stability, and single inorganic photochromic materials, which have good stability but slow response. The organic-inorganic composite system can simultaneously take into account both response speed and stability, and is the preferred technical solution of this invention.

[0057] A comparison of Example 1 and Comparative Example 1 shows that, after removing the spiropyran derivative, the color-changing efficiency ΔE*ab of Comparative Example 1 is only 0.5, almost completely losing its photochromic ability, while its antibacterial rate, total migration, tensile strength, and impact strength are basically the same as those of Example 1. This result indicates that the photochromic function does indeed originate from the added photochromic material, and also shows that the introduction of the photochromic component did not negatively affect the antibacterial properties, mechanical properties, and food contact safety of the matrix.

[0058] A comparison of Example 1 and Comparative Example 2 shows that, without the addition of the silver-zinc loaded inorganic antibacterial agent, Comparative Example 2 exhibits antibacterial rates of only 5.2% and 4.8% against Escherichia coli and Staphylococcus aureus, respectively, demonstrating almost no antibacterial effect. Furthermore, its color-changing response time, decolorization time, color-changing efficiency, and cycle stability remain virtually unchanged compared to Example 1. This comparison indirectly confirms that the antibacterial function is entirely provided by the inorganic antibacterial system. It also demonstrates that the introduction of the antibacterial component does not quench or interfere with the response behavior of the photochromic component. The two components can function independently within the same matrix, effectively overcoming the technical problem of mutual interference between the antibacterial agent and the color-changing component described in the background art.

[0059] A comparison of Example 1 and Comparative Example 3 shows that, in Comparative Example 3, where no dispersant was used and the spiropyran derivative was directly dry-mixed with polypropylene and extruded, the color-changing efficiency decreased from 35.2 to 22.4, a reduction of 36%. Cyclic stability decreased from 92% to 78%, while tensile strength decreased from 32.5 MPa to 29.5 MPa and impact strength decreased from 6.8 kJ / m² to 5.8 kJ / m². 2The total migration was 8.2 mg / dm³ 2 Rising to 9.8 mg / dm 2 The levels are approaching the standard limit. This is because photochromic powders, inorganic antibacterial powders, and nano-reinforced fillers are all nanoscale, and without dispersants, they are prone to agglomeration. Agglomerates not only reduce the effective area of ​​the color-changing component, weakening color-changing efficiency and fatigue life, but also form stress concentration points in the matrix, leading to a decrease in mechanical properties and increasing the local accumulation of additives, thus promoting migration. This demonstrates that dispersants are not merely optional processing aids, but essential functional components that simultaneously determine color-changing efficiency, cycle stability, mechanical properties, and migration safety.

[0060] A comparison of Example 1 and Comparative Example 4 shows that in Comparative Example 4, after replacing the inorganic silver-zinc loaded antibacterial agent with an equal mass of the conventional organic antibacterial agent OBPA, the antibacterial rates against Escherichia coli and Staphylococcus aureus decreased to 92.8% and 91.6%, respectively, failing to reach the antibacterial target of 99.9%. Simultaneously, the total migration decreased from 8.2 mg / dm³. 2 It rose sharply to 12.5 mg / dm³ 2 This exceeds the 10 mg / dm³ limit specified in GB4806.7-2023. 2 The fundamental reason for this limitation is that organic antimicrobial agents are prone to thermal decomposition and inactivation at extrusion temperatures of 180 to 230°C, and their small molecule characteristics make them highly susceptible to migration into food simulants. This comparison shows that conventional organic antimicrobial agents cannot simultaneously meet the dual requirements of high-efficiency antimicrobial activity and food contact safety, thus conversely confirming the necessity and irreplaceability of the inorganic silver-zinc-supported antimicrobial system selected in this invention.

[0061] A comparison of Example 1 and Comparative Example 5 shows that while Comparative Example 5, by replacing the spiropyran derivative with an equal mass of single nano-tungsten trioxide, achieved a 95% cycle stability and a 97% ΔE*ab retention rate after high-temperature processing, demonstrating excellent heat resistance, the color-changing response time increased to 52 seconds, the decolorization time reached 110 seconds, and the color-changing efficiency decreased to 26.3. This severe degradation in response speed fails to meet the rapid visual indication requirements of packaged products such as fresh produce and fruits that rely on real-time light-based freshness monitoring. This comparison illustrates that pure inorganic photochromic materials, constrained by the inherently slow lattice carrier migration dynamics, cannot achieve the rapid color-changing response sought by this invention, even with outstanding thermal stability. This highlights the significant advantages of this invention, particularly the preferred organic and organic-inorganic composite systems.

[0062] A comparison of Example 1 and Comparative Example 6 shows that, without the addition of antioxidants, the color-changing efficiency of Comparative Example 6 decreased from 35.2 to 24.5, the cycle stability plummeted from 92% to 68%, and the ΔE*ab retention rate after high-temperature processing decreased from 78% to 55%. Simultaneously, the tensile strength decreased to 28.3 MPa, the impact strength decreased to 5.2 kJ / m², and the total migration increased from 8.2 mg / dm² to 11.2 mg / dm², exceeding the standard limit. The mechanism lies in the significant thermo-oxidative degradation of polypropylene resin and organic color-changing molecules under the high temperature and oxygen conditions of screw extrusion. This not only directly destroys the color-changing molecular structure and weakens the mechanical properties of the resin matrix, but the small molecules produced by degradation also become the direct source of the excessive migration. This comparison couples the seemingly independent issues of processing thermal stability and food contact safety into the same causal chain, fully demonstrating the crucial role of the hindered phenol and phosphite compound antioxidant system in ensuring high-temperature processing stability, finished product mechanical properties, and food safety.

[0063] A comparison of Example 3 and Comparative Example 7 shows that after eliminating the organic-inorganic hybrid structure and using an equal mass of pure spiroxazine in Comparative Example 7, the initial color change response time was 25 seconds and the color change efficiency ΔE*ab was 36.8, slightly better than the 28 seconds and 32.8 of Example 3. However, after 500 cycles, the efficiency retention rate decreased from 94% to 70%, and after high-temperature processing, the ΔE*ab retention rate decreased from 90% to 62%, while the total migration increased from 8.0 mg / dm² to 9.6 mg / dm². It is worth noting that the actual amount of spiroxazine used in Example 3 was only 2 parts, while in Comparative Example 7 it was 4 parts. If the nano-titanium dioxide only served as an inert dilution, the color change efficiency should have decreased approximately linearly to about 18.4 as the concentration of the organic component was halved. However, the measured value reached 32.8, with a decrease of less than 11%, which is far better than the linear expectation. The reason lies in the fact that the nano-titanium dioxide carrier, through physical coating and isolation, blocks the direct contact between organic color-changing molecules and high temperature and oxygen, significantly inhibiting their thermal degradation and photo-fatigue, while simultaneously restricting the migration of organic components into food simulants. This result demonstrates that the organic-inorganic hybrid structure employed in this invention, without sacrificing response speed or color-changing amplitude, unexpectedly and significantly improves the heat processing stability and fatigue resistance of the photochromic components. This is the core innovation that distinguishes this invention from existing technologies.

[0064] Based on the comparative analysis of the above embodiments and comparative examples, it can be seen that the present invention, through the synergistic compounding of seven components—polypropylene resin carrier, photochromic material, antibacterial agent, dispersant, antioxidant, processing aid, and nano-reinforced filler—and especially through the synergistic effect of the organic-inorganic hybrid photochromic system, the inorganic silver-zinc loaded antibacterial system, and the dispersant and antioxidant, systematically solves multiple technical problems of existing photochromic polypropylene materials, such as slow color change and decolorization speed, insufficient antibacterial performance, poor processing thermal stability, dispersion and agglomeration of functional fillers, and excessive migration of additives that do not meet food contact standards. It achieves a unified technical effect of rapid photochromic response, high-efficiency antibacterial properties, excellent food contact safety, and processing stability.

[0065] The above descriptions are merely embodiments of the present invention, and common knowledge such as specific technical solutions and / or characteristics are not described in detail here. It should be noted that those skilled in the art can make various modifications and improvements without departing from the technical solutions of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the implementation of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.

Claims

1. An antibacterial photochromic polypropylene masterbatch, characterized in that: The raw materials, by weight, include 60-85 parts of polypropylene resin carrier, 0.5-10 parts of photochromic material, 1-5 parts of antibacterial agent, 0.5-3 parts of dispersant, 0.1-1 parts of antioxidant, 0.5-2 parts of processing aid, and 2-10 parts of nano-reinforcing filler.

2. The antibacterial photochromic polypropylene masterbatch according to claim 1, characterized in that: The photochromic material is one of organic photochromic materials, inorganic photochromic materials, and organic-inorganic composite photochromic materials; the organic photochromic material is at least one of spiropyran derivatives, spiroxazine derivatives, azobenzene derivatives, and diarylethylene derivatives; the inorganic photochromic material is at least one of nano-WO3, nano-TiO2, and calcium fluoride doped with rare earth ions; the organic-inorganic composite photochromic material is a spiropyran / nano-TiO2 hybrid material or an azobenzene / montmorillonite intercalation composite material.

3. The antibacterial photochromic polypropylene masterbatch according to claim 2, characterized in that: The antibacterial agent is a silver-zinc inorganic antibacterial agent, a silver ion antibacterial agent, or a zinc ion antibacterial agent.

4. The antibacterial photochromic polypropylene masterbatch according to claim 3, characterized in that: The antioxidant is at least one of hindered phenolic antioxidants and phosphite antioxidants.

5. The antibacterial photochromic polypropylene masterbatch according to claim 4, characterized in that: The antioxidant is a compound system of hindered phenolic antioxidants and phosphite antioxidants.

6. The antibacterial photochromic polypropylene masterbatch according to claim 5, characterized in that: The processing aids include at least one of zinc stearate, white oil, and solid paraffin; the nano-reinforcing filler is at least one of nano talc, nano titanium dioxide, and nano kaolin.

7. A method for preparing an antibacterial photochromic polypropylene masterbatch according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Weigh the polypropylene resin, photochromic material, antibacterial agent, dispersant, antioxidant, processing aid and nanofiller according to the formula ratio; S2. Mix the above raw materials in a high-speed mixer; S3. The mixture is fed into a twin-screw or four-screw extruder, and after melt blending, extrusion, water cooling and pelletizing, masterbatch granules are obtained.

8. A method for preparing an antibacterial photochromic polypropylene masterbatch according to claim 7, characterized in that: In step S3, the extrusion process parameters are: screw temperature 180-230℃, main machine speed 200-400 r / min, and vacuum degree -0.05 to -0.08 MPa.

9. The application of an antibacterial photochromic polypropylene masterbatch according to any one of claims 1 to 6 in the preparation of food packaging materials.